STATISTIK NON PARAMETRIK UNTUK MEMBANDINGKAN PEMBAGIAN FUNGSI KAWASAN DENGAN PENGGUNAAN LAHAN - Ani Apriani (UPT Penerbitan Universitas Jember, 2022)
The increases population has resulted in a lot of land being used as residential areas. Whereas Indonesia's topography is very diverse, such as mountains, hills, and plains. Uncontrolled land use by the community can cause various disasters including landslides and floods. Therefore, it is necessary to divide the functional areas starting from the protected function area, the buffer function area, the annual plant cultivation function area and the cultivation and settlement function area. Each of these functional areas has criteria and should stand on their respective functions. The purpose of this study is to analyze whether the division of area functions that have been carried out is in accordance with their use by the community. The research is descriptive quantitative approach and comparative test (Mann Whitney). For the 95% confidence level and the two-sided test, the Z table value is ±1.96. Because the calculated Z value (-1.559) > -1.96 and also comparing Asymp .Sig shows the number 0.119 > 0.05, the decision is to accept Ho. Thus, it can be concluded that there is no significant difference between the division of area functions and land use in Kalibawang District, Kulon Progo Regency, Yogyakarta. Keywords: area function, land use, statistics.